Environmental Forensics - Morrison, Robert Daniel (CRC Press, 2009)
Offering state-of-the-art techniques for both attorneys and environmental scientists, Environmental Forensics: Principles and Applications discusses non-chemical methods such as corrosion modeling, inventory reconciliation, and aerial photography interpretation. The book also covers chemical fingerprinting used to identify the origin and age of a contaminant release- relevant techniques include the use of radioactive isotope analysis, degradation modeling based on half-lives, and fuel additives such as MTBE.